Tinjauan Hukum Sayembara Dalam Islam Terhadap Kegiatan Mulung Koin Pada Live Streaming Tiktok - Cholilah, Zahirotu; Irfan, Muh. (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
TikTok is a social media platform supported with music features, filters, and various other creative features. Recently TikTok added a new feature that allows users to use the TikTok Live or live streaming feature. Live TikTok enables creators and users to communicate directly. TikTok Live also allows viewers to receive TikTok coins as a commission for activities that have been carried out, such as collecting coins during live streams organized by TikTokers or viewers. The organizer can also set the number of spectators who receive coins as they wish, so that not all spectators who press the treasure chest icon will receive coins. Therefore, the purpose of this study is to find out how the law of competition in Islam is against the activity of mulung koin on TikTok live streaming. This research is field research using a qualitative approach. The data collection method in this study uses observation and documentation methods. Data analysis was carried out using the theory proposed by Miles, Huberman, and Saldana, using techniques such as data condensation, data display, and drawing conclusions. The results of the study show that live streaming of the TikTok application according to Islamic sharia is included in the ju'alah/competition contract. Judging from the terms and conditions of the ju'alah contract, this mulung koin activity has been fulfilled. However, the organizer of the mulung koin should explain the harmony and conditions of the ju'alah contract that the salary or wages in the contract are not divided equally among each scavenger so as not to cause doubts.